Africa Rising: Orange-fleshed Sweetpotato Scaling Out in Zambia with new varieties in the pipeline - International Potato Center (2017)
In 2016/17, 6,000 households received orange-fleshed sweetpotato (OFSP) planting material during the rainy season. Through radio adverts, over a million listeners were reached with OFSP nutrition, production and marketing adverts. In collaboration with Zambia Agricultural Research Institute (ZARI) two clones - NC 09-350MUSG and Zambezi/2 were identified as elite genotypes based on farmers’ evaluation of agronomic and organoleptic attributes.